Clinical features of incidental mild cognitive impairment and dementia in a population‐based study. Issue 5 (6th May 2016) - Hishikawa, Nozomi; Fukui, Yusuke; Sato, Kota; Yamashita, Toru; Ohta, Yasuyuki; Abe, Koji
Abstract : Aim: The number of people with dementia is rapidly increasing as populations around the world age. It is important to grasp the characteristic features of mild cognitive impairment (MCI) for early detection and prevention of dementia. Methods: We examined 408 individuals recruited from a health checkup for metabolic syndrome, which comprised three groups: normal ( n  = 325), MCI ( n  = 55) and apparent cognitive decline (ACD; n  = 28). We compared cognitive/affective functions and exercise/hobby habits with assessments of vascular risk factors and results from computerized touch‐panel tests. Results: Among the 408 individuals, 93.1% showed normal scores on the Mini‐Mental State Examination, and 6.9% had ACD. Among the normal Mini‐Mental State Examination participants, 14.5% had MCI (13.5% of all participants). The three groups of participants showed significant differences in age, education, systolic blood pressure, glycosylated hemoglobin and high‐density lipoprotein cholesterol level. Even within the normal range, those in the MCI group showed significantly lower cognitive function than those in the normal group. Scores on the Geriatric Depression Scale were greater in the MCI group, and "day–night reversal" was worse in the ACD group. Scores on touch‐panel screening tests were significantly worse in the MCI and ACD groups than in the normal group. Participants showed better cognitive and affective function if they exercised regularly or had hobbies. Conclusions: Incidental MCI and ACD had prevalences of 13.5% and 6.9%, respectively, in the population‐based study. Participants with these conditions showed cognitive/affective decline and impairment on computerized touch‐panel tests in relation to vascular risk factors and exercise/hobbies.Geriatr Gerontol Int 2017; 17: 722–729 .